Development and validation of circulating tumour cell enumeration (Epic Sciences) as a prognostic biomarker in men with metastatic castration-resistant prostate cancer. (June 2021) - Scher, H.I.; Armstrong, A.J.; Schonhoft, J.D.; Gill, A.; Zhao, J.L.; Barnett, E.; Carbone, E.; Lu, J.; Antonarakis, E.S.; Luo, J.; Tagawa, S.; dos Anjos, C.H.; et al.
Abstract: Purpose: To evaluate the prognostic significance of circulating tumour cell (CTC) number determined on the Epic Sciences platform in men with metastatic castration-resistant prostate cancer (mCRPC) treated with an androgen receptor signalling inhibitor (ARSI). Patients and methods: A pre-treatment blood sample was collected from men with progressing mCRPC starting either abiraterone or enzalutamide as a first-, second- or third-line systemic therapy at Memorial Sloan Kettering Cancer Center (Discovery cohort, N = 171) or as a first- or second-line therapy as part of the multicenter PROPHECY trial (NCT02269982) (Validation cohort, N = 107). The measured CTC number was then associated with overall survival (OS) in the Discovery cohort, and progression-free survival (PFS) and OS in the Validation cohort. CTC enumeration was also performed on a concurrently obtained blood sample using the CellSearch® Circulating Tumor Cell Kit. Results: In the MSKCC Discovery cohort, CTC count was a statistically significant prognostic factor of OS as a dichotomous (<3 CTCs/mL versus ≥ 3 CTCs/mL; hazard ratio [HR] = 1.8 [95% confidence interval CI 1.3–3.0]) and a continuous variable when adjusting for line of therapy, presence of visceral metastases, prostate-specific antigen, lactate dehydrogenase and alkaline phosphatase. The findings were validated in an independent datas et from PROPHECY (HR [95% CI] = 1.8 [1.1–3.0] for OS and 1.7 [1.1–2.9] for PFS). A strong correlation was also observed between CTC counts determined in matched samples on the CellSearch® and Epic platforms (r = 0.84). Conclusion: The findings validate the prognostic significance of pretreatment CTC number determined on the Epic Sciences platform for predicting OS in men with progressing mCRPC starting an ARSI. Highlights: In this study, a CTC is any CK+, CD45- cell and clusters are counted as one event. The findings validate CTC count on the Epic platform as a prognostic biomarker. Comparable associations with OS and PFS were observed using CellSearch®..